The effect of aerobic exercises and stragol consumption on plasma levels of IL-6, TNFα and IL-10 following a myocardial infarction in male wistar rats - Iman Zakavi; Jamshid Banaii Broojeni2; Saeed Keshavarz; Elham Eftekhari (فصلنامه ابن سینا, 2023)
Background and aims: Stragol herbal composition and aerobic exercise may have additional positive effect on inflammation process after myocardial infarction (MI). So, this study aimed to analyze the effect of aerobic exercise and stragol consumption on plasma levels of IL-6, TNF-α, and IL-10 following a MI in male Wistar rats. Methods: Male wistar rats were subjected to coronary artery occlusion surgery and then MI was confirmed by electrocardiography. Totally, 32 male rats (aged 8-10 weeks) were randomly devided into four groups. The aerobic exercises has lasted for six weeks (three training sessions in every week). Stragol consumption group as well as combined group have received 9.58 mL/day of stragol drop. The data has been analyzed according to one-way ANCOVA test and Bonferroni test. Results: None of the interventions had a significant difference on IL-10 and TNF-α. But there was a significant impact between the adjusted mean IL-6 in all studied groups (p=0.003). The aerobic exercises and stragol had no significant impact on IL-6 separately whereas the combined intervention decreased IL-6 following a MI in rats (p=0.003). Conclusion: It seems that aerobic exercises and administration of stragol drops is a combination that can improve the inflammatory state after MI.